Study of Functional Changes in the Liver of Male Hamsters Treated with the Antibiotic Amoxicillin and the Possible Protective Effect of Sidr Honey - Salma Al-Abyad,; Abdulrahman Abduldayem,; Wafaa Al-Drouqi, (AlQalam Journal of Medical and Applied Sciences, 2024)
The present study aimed to identify the functional changes in the liver of male hamsters treated with the antibiotic amoxicillin and to investigate the potential preventive and therapeutic effect of Sidr honey against the hepatotoxicity induced in experimental animals by the antibiotic. (28) male hamsters were used in this study, divided into 4 groups, the first group (negative control) was dosed with distilled water - the second group (positive control) was dosed with antibiotic only at a concentration of (50 mg/kg) - the third group (treated with honey as a treatment with antibiotic) was dosed daily with honey at a concentration of (2 g/kg) simultaneously with antibiotic at a concentration of (50 mg/kg) - the fourth group (treated with honey as a preventive measure then antibiotic) the individuals of this group were dosed daily with honey at a concentration of (2 g/kg) and then they were dosed with antibiotic at a concentration of (50 mg/kg) three times a week simultaneously with honey. The results of the current study showed a significant increase in the activity level of liver enzymes AST, ALT, ALP, and GGT, as well as albumin, bilirubin, urea, and uric acid in the positive control group (treatment with the antibiotic amoxicillin only). As for the third group, in which honey was used as a treatment, some vital parameters improved (AST, albumin, bilirubin, and uric acid), while other vital parameters remained high (ALT, ALP, GGT, and urea). As for the fourth group, which was treated with honey as a preventive measure for 3 weeks before dosing the animals with the antibiotic, there was a noticeable improvement in most vital parameters, as AST, GGT, albumin, bilirubin, uric acid, and urea decreased significantly (p<0.05). The results of microscopic examination of liver tissue in the group treated with antibiotics only showed severe damage to liver tissue, which appeared in the form of severe cellular necrosis, dilation of the walls of blood vessels, especially in the central vein, and widening and protrusion of the prominent sinusoidal blood vessels and their congestion with blood. As for the fourth group, the histological examinations improved significantly compared to the second and third groups. هدفت الدراسة الحالية للتعرف على التغييرات الوظيفية في كبد ذكور الهامستر المعاملة بالمضاد الحيوي الاموكسيسلين و تقصي التأثير الوقائي و العلاجي المحتمل لعسل السدر ضد السمية الكبدية المستحدثة لحيوانات التجربة بالمضاد الحيوي. استخدم في هذه الدراسة (28) من ذكور الهامستر، قسمت الى 4 مجموعات , المجموعة الاولى (الضابطة السلبية) جرعت بالماء المقطر- المجموعة الثانية (الضابطة الإيجابية) جرعت بالمضاد الحيوي فقط بتركيز (50 مغم/ كجم) - المجموعة الثالثة ( معاملة بالعسل كعلاجي مع المضاد الحيوي ) حيث جرعت يوميا بالعسل بتركيز (2غم/كجم) وذلك بالتزامن مع تجريعها بالمضاد الحيوي بتركيز (50 مغم/كجم ) - المجموعة الرابعة ( معاملة بالعسل كوقائي ثم المضاد الحيوي ) جرعت افراد هذه المجموعة يوميا بالعسل بتركيز (2غم/كجم) ومن ثم تم تجريعها بالمضاد الحيوي بتركيز (50 مغم/كجم ) ثلاث مرات اسبوعيا بالتزامن مع تجريعها بالعسل. اظهرت نتائج الدراسة الحالية حدوث ارتفاع معنوي في مستوى نشاط انزيمات الكبد AST و ALT و ALPو GGT و كذلك الالبومين و البيليروبين و اليوريا وحمض البوليك في المجموعة الضابطة الاجابية ( المعاملة بالمضاد الحيوي الاموكسيسلين فقط )، اما المجموعة الثالثة التي استخدم فيها العسل كعلاج تحسنت فيها بعض المعايير الحيوية (AST , الألبومين , البيليروبين, وحمض البوليك ) وبقاء المعايير الحيوية الاخرى مرتفعة (ALT وALP و GGTواليوريا)، اما المجموعة الرابعة والتي عوملت بالعسل كوقائي لمدة 3 اسابيع قبل تجريع الحيوانات بالمضاد الحيوي حدث فيها تحسن ملحوظ في معظم المعايير الحيوية فقد انخفض كلا من AST و GGT والالبومين والبيليروبين وحمض البوليك واليوريا انخفاضا معنويا p<0.05. كذلك بينت نتائج الفحص المجهري لنسيج الكبد في المجموعة المعاملة بالمضاد الحيوي فقط حدوث تلفا شديدا لنسيج الكبد ظهر بصورة تنخر خلوي شديد و تمدد في جدران الاوعية الدموية خصوصا في الوريد المركزي واتساع وبروز في الجييبينات الدموية Prominent sinusoidal واحتقانها بالدم. اما المجموعة الرابعة فقد تحسنت فيها الفحوصات النسيجية تحسناً ملحوظا بالمقارنة مع المجموعة الثانية والثالثة